ANALYSIS OF COMMUNICATION STRATEGY IN INCREASING ALUMNI PARTICIPATION IN FILLING TRACER STUDY ALUMNI (TSA) AS A CONTRIBUTION TO THE ACHIEVEMENT OF MAIN PERFORMANCE INDICATORS (IKU) IN THE COMMUNICATIONS STUDY PROGRAM FISIP UNTIRTA - Atih Ardiansyah; Ivan Issa Fathony; Deana Derawati; Vanessa Devara Ardine (Sean Institute, 2023)
Tracer Study Alumni (TSA) is a popular tool in efforts to continuously improve higher education institutions. In the Untirta FISIP Communication Studies Program, which has become Untirta's favorite major in the National Selection to Enter State Universities, Joint Selection to Enter State Universities and Independent Selection in the Western Region for two consecutive years, namely 2021-2022, the level of alumni participation in filling out the TSA formula is still below 50 percent. This has an impact on the low achievement of the Main Performance Indicators (IKU) of the FISIP Communication Studies Study Program in the 2022 Untirta Internal IKU League, especially IKU 1 concerning